1997
DOI: 10.1300/j023v10n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Solvent Use: Patterns by Gender and Ethnicity Among School Attenders and Dropouts

Abstract: Differences in patterns of volatile solvent use were explored with special emphasis on use as related to school enrollment status. The sample included American Indian, Mexican-American and White American youth. Furthermore, three enrollment status categories were identified: dropout, academically at-risk (enrolled), and control. A self report survey was used to assess both level and intensity of volatile solvent use. Findings indicated that a higher proportion of the dropout cohort have used volatile solvents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
(26 reference statements)
2
8
0
Order By: Relevance
“…Similar findings have been reported for later use of injectible drugs (Dinwiddie, Reich, & Cloninger, 1991) and heroin (Johnson, Schutz, Anthony, & Ensminger, 1995). Inhalant use has also been linked to negative consequences that include low academic performance (Bates, Plemons, Jumper-Thurman, & Beauvais, 1997), delinquency (Mackesy-Amiti & Fendrich, 2000), elevated rates of childhood aggressiveness, and alcohol dependency (Howard, Walker, Walker, Cottler, & Compton, 1999). Howard and Jenson (1999) noted that inhalant use was a marker for suicidal and criminal behaviors and family problems.…”
Section: Introductionsupporting
confidence: 62%
“…Similar findings have been reported for later use of injectible drugs (Dinwiddie, Reich, & Cloninger, 1991) and heroin (Johnson, Schutz, Anthony, & Ensminger, 1995). Inhalant use has also been linked to negative consequences that include low academic performance (Bates, Plemons, Jumper-Thurman, & Beauvais, 1997), delinquency (Mackesy-Amiti & Fendrich, 2000), elevated rates of childhood aggressiveness, and alcohol dependency (Howard, Walker, Walker, Cottler, & Compton, 1999). Howard and Jenson (1999) noted that inhalant use was a marker for suicidal and criminal behaviors and family problems.…”
Section: Introductionsupporting
confidence: 62%
“…Several studies found high prevalence of VSM among female subjects and noted dissimilarities between the characteristics of the two genders (Bates, Plemons, Jumper-Thurman, & Beauvais, 1997). Treatment outcome studies of female volatile substance misusers are warranted.…”
Section: Limitationsmentioning
confidence: 99%
“…This finding supports the view that variables predictive of students' academic success are not limited to specific academic skills, but involve interpersonal competencies. Other stud ies correlated the higher proportion of school drop out to early onset cigarette smoking and drug use (Bray et al 2000;Bates et al 1997). This was con firmed by the study of Ferguson et al (1997), where he found a strong association between early onset (prior to 16 years of age) cannabis use and subse quent affiliations with delinquent and substanceusing peers, resulting in a move away from home and school dropout.…”
Section: General Characteristic Of School Drop Outmentioning
confidence: 85%